2018
DOI: 10.1111/mec.14871
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive significance of chromosomal inversion polymorphisms inDrosophila melanogaster

Abstract: Chromosomal inversions, structural mutations that reverse a segment of a chromosome, cause suppression of recombination in the heterozygous state. Several studies have shown that inversion polymorphisms can form clines or fluctuate predictably in frequency over seasonal time spans. These observations prompted the hypothesis that chromosomal rearrangements might be subject to spatially and/or temporally varying selection. Here, we review what has been learned about the adaptive significance of inversion polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
181
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(192 citation statements)
references
References 220 publications
(289 reference statements)
8
181
0
Order By: Relevance
“…Inversions can create large areas of restricted recombination as they prevent proper chromatid pairing, although gene conversion and double cross-overs may allow some genetic exchange between inverted and non-inverted haplotypes (Andoflatto, Depaulis, & Navarro, 2001). Empirical studies have inversions contributing to local adaptation for instance in D. melanogaster (Kapun & Flatt, 2018), sticklebacks (Jones et al, 2012), yellow monkeyflower (Gould, Chen, & Lowry, 2018), teosinte (Tanja Pyhäjärvi, Hufford, Mezmouk, & Ross-Ibarra, 2013), humans (Puig, Casillas, Villatoro, & Cáceres, 2015) and in many others (Wellenreuther & Bernatchez, 2018).…”
Section: Linkage Disequilibrium Patterns and Putative Large Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inversions can create large areas of restricted recombination as they prevent proper chromatid pairing, although gene conversion and double cross-overs may allow some genetic exchange between inverted and non-inverted haplotypes (Andoflatto, Depaulis, & Navarro, 2001). Empirical studies have inversions contributing to local adaptation for instance in D. melanogaster (Kapun & Flatt, 2018), sticklebacks (Jones et al, 2012), yellow monkeyflower (Gould, Chen, & Lowry, 2018), teosinte (Tanja Pyhäjärvi, Hufford, Mezmouk, & Ross-Ibarra, 2013), humans (Puig, Casillas, Villatoro, & Cáceres, 2015) and in many others (Wellenreuther & Bernatchez, 2018).…”
Section: Linkage Disequilibrium Patterns and Putative Large Inversionmentioning
confidence: 99%
“…melanogaster (Kapun & Flatt, 2018), sticklebacks (Jones et al, 2012), yellow monkeyflower (Gould, Chen, & Lowry, 2018), teosinte (Pyhäjärvi, Hufford, Mezmouk, & Ross-Ibarra, 2013) and in butterfly mimicry (Kunte, 2014).…”
Section: Linkage Disequilibrium Patterns and Putative Large Inversionmentioning
confidence: 99%
“…Since these inversions show latitudinal and longitudinal gradients in the americana complex, it is likely that they carry the targets of selection associated with local adaptation in natural populations. For instance, chromosomal inversions were found to be associated with life-history and physiological traits likely involved in adaptation (Huang et al 2014; Durmaz et al 2018; Kapun and Flatt 2019) as well as with morphological traits (Norry et al 1995; Fernández Iriarte et al 2003; Rako et al 2006; Hatadani and Klaczko 2008). Additionally, a previous study found that the fixed variant explaining pigmentation differences between D. novamexicana and D. americana was polymorphic in D. americana and explained the least pronounced variation in pigmentation observed along a longitudinal transect in D. americana populations (Wittkopp et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chromosomal inversions can act as super genes influencing a myriad of phenotypes that can have a large adaptive value. The impact of chromosomal inversions on many life-history and physiological traits is well established and is often associated with local adaptation (Huang et al 2014; Durmaz et al 2018; Fuller et al 2019; Kapun and Flatt 2019). Additionally, chromosomal inversions are associated with differences in rather simple morphological traits.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, genome reshuffling has important evolutionary and ecological implications, since gene flow can be reduced within the reorganized regions in the heterokaryotype, thus affecting co-adapted genes locked within the rearrangement that, if advantageous, increase in frequency in natural populations (reviewed in [1]). In fact, evidence on the role of large-scale chromosomal changes in adaptation and diversification has been reported, especially in the case of inversions [2][3][4][5]. As for chromosomal fusions, however, empirical studies are limited to the house mouse (Mus musculus domesticus) and shrews (Sorex araneus), two mammalian systems where the presence of chromosomal fusions (either fixed or in polymorphic state within populations) are widespread [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%